IMPLEMENTASI DAN FORMULASI STRATEGI MANAJEMEN RISIKO PADA UNIT USAHA SAPI PERAH DAN PRODUKSI SUSU KUD SARWA MUKTI - Sugiyanto Sugiyanto; Dewi Puspita Arum; Anggi Andriani Rahayu (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2021)
Abstract - Cooperatives as business entities cannot be separated from various risks that must be present, uncertainty is difficult to predict and can cause losses. Risk management needs to be implemented to see the impact, in order the organization goals can be achived. Risk management has not been implemented in many cooperative business entities. The purpose of this research is to identify, map and formulate risk management strategies in Dairy Cattle and Milk Production Business. The research method used is a case study. The results of this study identified 17 possible events of risk. The 13 risks are categorized as